Prototype of Information System of Medical Record Borrowing and Return in Puskesmas - Yunus, Muhammad; Andriani, Firdha Trisna (Journal of Digital Literacy and Volunteering, 2023)
The borrowing and returning of medical records carried out at Puskesmas X is still done manually, there is no recording of medical records in and out of the expedition book in the MR unit which makes it difficult for officers to find patient medical records borrowed by the poly. The ineffectiveness of these activities hampers officer work and patient service activities if MR file has not returned to the MR room within 1x24 hours. Recording patient identity is still done manually using books and Excel so that double recording occurs which is considered ineffective by officers. In addition, the numbering of MR is recorded manually into a book based on the village code in Puskesmas X so that it is prone to number errors. The purpose of this study is to design an information system for borrowing and returning medical record files at Puskesmas X Pasuruan Regency to solve these problems. This type of research is Research and Development with the waterfall method and data collection through observation and interviews. The result of this research is a MR file loan and return information system that can facilitate the performance of MR officers at Puskesmas.